The isolation and characterization of Campylobacter-specific bacteriophages from porcine origin - Lis, Lukas (2017)
Campylobacter jejuni represents a major foodborne pathogen causing gastroenteritis worldwide. The infection route to the consumer is primarily associated with improper handling of raw meat of poultry and porcine origin. Biocontrol of this pathogen through conventional biosecurity measures remains challenging. Alternative bacteriophage-based strategies for the reduction of campylobacters in primary production and post-harvest have gained attention in recent years, as a number of promising biocontrol studies have emerged. However, the effective application of bacteriophage cocktails relies on an extensive characterization of suitable bacteriophage candidates, as well as detailed information related to host-phage interactions during the phage infection process. In this project, bacteriophages were isolated from numerous environmental samples and characterized with respect to host interactions. Inclusion of source material from the porcine intestinal tract revealed that the genetic diversity of bacteriophages exhibits similar limitations to that observed from poultry. All bacteriophage isolates were found to be members of either the CP220like or CP8unalike genera of the Eucampyvirinae subfamily of bacteriophages. The screening of isolated bacteriophages against a panel of isogenic single gene knock-out mutants of C. jejuni PT14 revealed that the phages were either flagellotropic or dependent on capsular polysaccharides (CPS). In one case, both factors showed a fundamental impact on bacteriophage infection. Further, it was discovered that the minor flagellin gene product (FlaB) had profound influence on the infection process of novel isolated CP8unalike phage CP_F1. Disruption of the flaB gene resulted in alterations in a number of parameters (burst size and adsorption rate) connected with bacteriophage infection, and in essence rendered the affected mutant strain more susceptible towards phage infection. Sequence analysis of CP220like bacteriophage genomes demonstrated variability in the length and frequency of regions of repetitive non-coding DNA. These are a characteristic of CP220like phages and are absent in CP8unalike phages. Deeper in silico analysis of these areas revealed potential binding sequences for all three sigma factors of C. jejuni. Through electro mobility shift assays, it was shown that a PCR amplified repeat area binds to components from a protein extract isolated from a phage infected culture of C. jejuni. This finding raises questions concerning novel control mechanisms of the host during bacteriophage infection.